Parental influences on primary school children’s mathematics achievement: Insights from the Longitudinal Study of Australian Children (LSAC) - MacDonald, Amy; MacDonald, A; Carmichael, Colin (My University, 2016)
Results from international mathematics tests are focussing the attention of national leaders on the learning of mathematics in the primary years. With this attention, comes the need to explore the factors that contribute to and impede this learning. Though much of this focus is on classroom practices, it is timely to examine the important influence that parents have on their children's achievement. This paper reports on a secondary analysis of data from a large longitudinal study in Australia; in particular, the effectiveness of Australian parents’ involvement in their children's homework. The results suggest that the actual help with homework has, on average, a negative effect on children's achievement even after controlling for earlier achievement. Significantly, however, the other types of involvement, such as provision of a good home environment, have positive effects on achievement. The implications of these findings are also discussed
Keywords: Education and Training -- Literacy and numeracy; Education and Training -- Primary; Families -- Parents and Parenting; Families and relationships; Learning, education and training; Families; Education and Training; Primary; Literacy and numeracy; Parents and Parenting; Families and relationships; Learning, education and training